2020
DOI: 10.1155/2020/8881177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Irrigating Devices on the Removal of Two Different Forms of Calcium Hydroxide from Internal Resorption Cavities

Abstract: The present study aimed to investigate the efficiency of passive ultrasonic irrigation (PUI), EndoActivator (EA), standard needle irrigation (SNI), and XP-endo Finisher files in removing pure calcium hydroxide (pCH) and injectable CH from in vitro root resorption cavities. Using a rotary system, the root canals of 116 extracted single rooted teeth were prepared. Imitated internal resorption cavities were then created in root halves. The specimens were divided into two groups according to the form of CH (n = 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…To keep the WL constantly irrigated, a negative pressure is used. The EndoVac and needle irrigation methods were investigated by Nielsen et al [ 23 ] for debriding the apical 3 mm of a root canal. There was no difference between the two irrigation systems at the apical 3-mm level.…”
Section: Reviewmentioning
confidence: 99%
“…To keep the WL constantly irrigated, a negative pressure is used. The EndoVac and needle irrigation methods were investigated by Nielsen et al [ 23 ] for debriding the apical 3 mm of a root canal. There was no difference between the two irrigation systems at the apical 3-mm level.…”
Section: Reviewmentioning
confidence: 99%
“…15 In many studies, passive ultrasonic irrigation has been shown to be highly effective in removing calcium hydroxide from root canals. 16,17 EDDY (VDW, Munich, Germany) is a recently developed irrigation device that uses sonic agitation. It is used with a polymer tip using a conventional air scaler with a frequency of 6000 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…As there are abundant studies of evidence ascertained that complete debridement of root canal through chemomechanical preparation, cleaning, and shaping is nearly impossible due to its intricate nature. [ 1 2 3 4 ] Therefore, the placement of calcium hydroxide (CH) as intracanal medication has been implemented to facilitate complete disinfection from the complex structures of the root canal. [ 1 2 5 6 ] Researchers have shown that remnants of CH on dentinal walls affect the penetration of sealers, increase apical leakage, and react chemically with obturating materials, thus interfering with their properties which cause compromising the quality of the seal provided by endodontic root filling materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 3 4 ] Therefore, the placement of calcium hydroxide (CH) as intracanal medication has been implemented to facilitate complete disinfection from the complex structures of the root canal. [ 1 2 5 6 ] Researchers have shown that remnants of CH on dentinal walls affect the penetration of sealers, increase apical leakage, and react chemically with obturating materials, thus interfering with their properties which cause compromising the quality of the seal provided by endodontic root filling materials. Therefore, the complete removal of CH from the root canal before obturation is recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation